Checklist of the Marine and Estuarine Brachyuran Crabs (Crustacea: Decapoda: Brachyura) of Andhra Pradesh, India - Kumar, J. S. Yogesh; Sen, Arya; Panda, Pradip (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
An account of the brachyuran crab diversity along the Andhra Pradesh coast of India has been represented in this communication. The checklist of brachyuran crabs has been prepared for the state of Andhra Pradesh based on reviews and compilation of published research works for this particular region. A total of 156 species belonging to 91 genera and 33 families have been listed here from Andhra Pradesh. Visakhapatnam showed the highest diversity with 86 species in all the marine areas and Vizianagaram has the lowest diversity recorded from the state with one species. Although the study on the brachyurans from Andhra Pradesh had been started from early 1800 but recent works on brachyurans from Andhra Pradesh is lacking and with a focused study from the area would help in exploration of brachyuran’s diversity from the east coast of India.